Association between Lamp Light During Sleep and Sleep Quality in Medical Students - Yurike, Vony; Harjanto, Bernardus Realino; Widjaja, Nelly Tina; Sidharta, Veronika Maria (Althea Medical Journal, 2024)
Background: Sleep quality is influenced by numerous factors, including external factors, such as the sleep environment. One aspect of the sleep environment that can influence sleep is lighting. Light exposure emitted by lamps during sleep can impair sleep quality. The aim of this study was to investigate the association between lamp light during sleep and sleep quality in preclinical medical students.Methods: This cross-sectional observational analytic study was carried out on 386 preclinical medical students who were determined using the cluster sampling method. Data was collected in November 2022. Lamp light during sleep and sleep quality among students were measured using the Indonesian version of the Pittsburgh Sleep Quality Index. The association between lamp light and quality of sleep was analyzed by the Chi-Square test.Results: There were 26.68% of students who used lights when sleeping. Poor sleep quality was detected in 46.37% of students. The association between lamp light during sleep and quality of sleep yielded a p-value of 0.002.Conclusion: There is a significant association between lamp light during sleep and sleep quality in preclinical medical students. Thus, improving sleep quality in preclinical medical students may be achieved by modifying the lamp light during sleep.